TEORI GRAF DALAM ANALISIS JEJARING SOSIAL: HUBUNGAN AKTOR UTAMA DENGAN PENGGUNA INTERNAL LAPORAN KEUANGAN - Sari, Martdian Ratna; Dwiyanti, Kadek Trisna (UI Scholars Hub, 2018)
The position of a person in a network or within an organization is not only determined by how many people are connected to a person, but another important point of focus is whether a person is the link or bridge of people who have multiple networks. Social Networking Analysis plays an important role in describing the interaction of informal human interaction as a real situation. The form of social network that can be analyzed in this research is the main actors preparing the financial statements up to the network use of financial statements. This study aims to analyze social networking on financial information dissemination structure based on company organizational structure in general and structure of finance division in particular. By using Gephi software, the structure of financial information dissemination is transferred into mathematical form (graph theory), is then analyzed and is taken conclusion from social networking that happened based on properties/features of the formed graph. The results concluded that the main actors in the network of organizational structure in the dissemination of financial information is the accounting and finance department that has the three largest information networks as information brokers, which are financial director, production director and personnel director.